Finance and Development, December 1983. (Finance and Development; Finance and Development ;, 1983)
This paper highlights the sources of payments problems in less developed countries. Growth in the industrial countries has a direct impact on the current account of the developing countries through its influence on both the prices and volumes of their exports. An increase in the real effective exchange rate is clearly a fundamental determinant of a deteriorating current account since, other things being equal, it tends to raise domestic demand for imports and to reduce foreign demand for exports.